The Medieval Muslim Cemeteries of Tigray (Ethiopia) - Simon Dorso; Anna Lagaron (Revue des Mondes Musulmans et de la Méditerranée)
The discovery (or rediscovery) and the archaeological excavation of the medieval Muslim cemetery of Bilet (Tigray, Ethiopia) in 2018, made it possible to study for the first time in the northern highlands of Ethiopia, the funerary architecture and burial rites of a Muslim community prior to the 8th/14th century. The data collected in Bilet, important for the knowledge of Ethiopian Islam before the great conquests of the sixteenth century, can now be compared locally to the unpublished corpus of contemporary cemeteries identified in the vicinity of Arra, which delivered important epigraphic material but were not excavated. This first review of the four Medieval Tigrayan cemeteries invites us to consider them in a broader regional context, in Ethiopia but also beyond, in the whole of the Horn of Africa and on the shores of the Red Sea, an area with which the epitaphs of Bilet attest important contacts. This contribution offers preliminary reflections on the materiality of the Tigrayan cemeteries through its lapidary (selection of supports, work, engraving and implementation of inscribed stelae) and architectural aspects (location of the funerary spaces, forms and organisation of grave markers, integration of the stelae within the markers).